Sound Governance in the Development of Mamminasata Metropolitan Areas in South Sulawesi Province - Firdaus Firdaus (Magister Ilmu Administrasi Publik, 2016)
The direction of development in Indonesia has strongly integrated with the concept of good governance started from the strengthening of international market that is both imperialist and colony thereby contradicting to the tradition of developing countries. This leads to the establishment of sound governance as an alternative concept to improve the government's capacity to innovate in policy and administration. The development of Mamminasata Metropolitan area in South Sulawesi province experiences difficulties in implementing the coordination, integration, synchronization and cannot accommodate the whole event in order to realize the interconnection of development across districts / cities, whereas the central government makes this as a National Strategic Areas (KSN) and leading area in the East Indonesia. This study aims to explore and analyze the sound governance practices in the development program of Mamminasata Metropolitan area focusing on five dimensions, namely process, structure, values, management, and policy. The results show that 1) in the process dimension, the stakeholders involved in the Mamminasata development program establish inter-regional cooperation and coordinate externally and internally of the area ranging from planning to the implementation of development activities; 2) in the structure dimension, the government has established clear organization and regulation in regulating the development process. 3) in the value dimension, Mamminasata development program is based on the responsiveness of local government and has up-holded justice in accordance with the potential of each area; 4) in the management dimension, the government personnel has already had knowledge about the Mamminasata concept, but they are still experiencing problems in the use of technology because of limited resources; and 5) in the policy dimension, the government has encouraged the public to participate directly in policy making and implementation of development programs. Therefore, it can be concluded that the five dimensions of sound governance has been practiced in the Mamminasata Metropolitan area development.